IoT E-Waste Monitoring System to Support Smart City Initiatives - Liaqat Ali, Nurul Aifah; Ramly, Ruwaida; Sajak, Aznida Abu Bakar; Alrawashdeh, Rula (International Journal of Integrated Engineering, 2020)
This project introduces the design and development of IoT E-waste monitoring system to support Green City initiatives in real-time. The main objective of this system is to design an IoT-based recycle e-waste monitoring system that will provide an efficient solution to electronics waste collection and generation data. The hazardous chemical components of e-waste have potentially adverse impacts on ecosystems and human health if not managed and monitored properly. Hence, the importance to constantly monitor the condition of the e-waste bin. The system measures and delivers up-to-date information to the system’s administrator on the waste level and bin’s current temperature in real-time. In case of fire, the system will give notification via its flame indicator. Agile Model is used as the research methodology as it offers an adaptive approach in respect to what features need to be developed. The proposed system consists of HC - SR04 Ultrasonic sensor which measures the waste level, a DS18B20 temperature sensor that detects the temperature in the bin, KY- 026 flame sensor, a Raspberry Pi 3 Model B+ as a microcontroller and ThingSpeak as an IoT web platform. ThingSpeak concurrently stores data for future use and analysis, such as prediction of the peak level of waste bin. This system is expected to increase the usage of e-waste recycle bin, hence supporting the Green City initiatives and creating a greener environment by monitoring and controlling the collection of e-waste smartly through the concept of Internet-of-Things (IoT).